PENGARUH SOCIAL MEDIA MARKETING DAN HARGA TERHADAP KEPUASAN PELANGGAN SOUND SYSTEM JUNIOR AUDIO - Fransiska Elsa Risa Kurniati; Antonius Phillipus K.Gheta; Kristiana Reinaldis Aek (Universitas Nusa Nipa Maumere, 2026)
Abstrack This study aimed to: (1) identify the description of social media marketing, price, and customer satisfaction; (2) analyze the influence of social media marketing and price on customer satisfaction both partially and simultaneously. The research method used was quantitative with an associative approach. Data were obtained through the distribution of questionnaires to customers and were analyzed using multiple linear regression with the assistance of SPSS 26. The population of this study was customers of Junior Audio Sound System, with a total of 72 respondents obtained through purposive sampling technique. The results of the study indicated that partially the social media marketing variable (X1) had a significant effect on customer satisfaction (Y). The price variable (X2) also had a significant effect on customer satisfaction (Y). Simultaneously, the social media marketing and price variables had a significant effect on customer satisfaction with Fcount > Ftable and a significance value of 0.000 < 0.05. The magnitude of the contribution of the social media marketing and price variables to customer satisfaction was 26.4%, while the remaining 73.6% was influenced by other factors outside the research variables. Keywords: Social Media Marketing, Price, Customer Satisfaction